Forage Adaptation in Ethiopian Mixed Farming Systems - Alene, Temesgen; Alemayehu, Liulseged; Mekonnen, Kindu (International Livestock Research Institute, 2024)
Feed is one of the major production inputs that affect the production and productivity of Livestock. In many parts of Ethiopia, animals are kept on poorquality natural pasture and crop residues. However, the contribution of natural pasture was declining from time to time as a result of the expansion of crop production, poor management and seasonal availability. One of the possible options to alleviate feed shortage is introducing and utilizing improved forage crops for the given production system. Improved forage crops species are very important because of their high biomass yield and good nutritional value. Adaptation trials of selected grass and legume forage varieties are currently underway at various MFS sites across Ethiopia. This report highlights the progress of the adaptation trials conducted at the MFS site in the North Shewa Zone of the Amhara region. Oat and vetch varieties have been chosen to diversify and intensify the mixed farming systems and provide food, feed and other products and services in the North Shewa frost prone and high-altitude areas.